Perfil bioquímico sérico de frangos de corte alimentados com dieta suplementada com óleos essenciais e pimenta - Traesel, Carolina Kist (2009)
Essential oils of natural origin and low cost have antimicrobial properties and can increase broilers performance, constituting an alternative to growth promoters based on antibiotics for poultry production; however, they can produce toxic effects. Serum biochemical parameters regarding to pancreatic, renal and hepatic functions of broiler chickens fed diets supplemented with antibiotics or essential oils of oregano, sage, rosemary and pepper aqueous crude extract (OLES) were evaluated. Animals (n=910) were distributed within five treatment groups with seven replicates of 26 birds each. Control group received a diet without additives; treatment Tatb received an antibiotic growth promoter diet; treatments T50, T100 and T150 received feed supplemented with 50, 100 and 150 ppm of OLES, respectively. At 42 days, 11 animals per group were slaughtered and blood samples were collected for serum biochemical profile analysis (lipase, amylase, urea, uric acid, aspartate aminotransferase - AST, gama glutamyltransferase, total cholesterol, high-density lipoprotein, low-density lipoprotein, triglycerides, total protein, albumin, globulins and albumin:globulins ratio). The results showed elevated serum lipase, uric acid, urea and AST, suggesting the impairment of kidney and liver functions caused by OLES. More studies are needed for essential oils dose adjustment in the diet, providing benefits without being harmful to the animal.